Anemia Status of Girls Adolescent and It’s Contributing Factors at Bekasi City, Indonesia - Muhammad Nur Hasan Syah; Alfi Fairuz Asna; Silvia Mawarti Perdana; Chioma Utah-Iheanyichukwu (Poltekkes Kemenkes Palu, 2025)
Background: Anemia remains a significant public health issue, particularly among adolescent girls, due to its impact on cognitive development, productivity, and reproductive health. This study aims to investigate the association between anemia status and specific contributing factors—including nutritional status (underweight, overweight/obese), dietary intake (staple food and protein consumption), and socioeconomic status (parental education, pocket money)—among adolescent girls aged 12–18 years in Bekasi, Indonesia. Methods: A cross-sectional study was conducted in 2018 across five high schools in Bekasi, involving 345 adolescent girls aged 12-18 years. Data were collected through food frequency questionnaires, anthropometric measurements, and hemoglobin level tests. Anemia was classified based on WHO guidelines. Statistical analysis included univariate, bivariate, and multivariate tests to identify significant predictors. Results: The prevalence of anemia among participants was 30.7% (95% CI: 25.9%–35.8%), with mild anemia being the most common type, accounting for 48.1% of anemic cases. Overweight or obese participants were significantly more likely to be anemic (OR = 3.52, 95% CI: 1.65–7.51, p = 0.001). Staple food consumption frequency also showed a significant association with anemia risk (OR = 1.75, 95% CI: 0.95–3.21, p = 0.070). However, no significant association was found between socioeconomic status and anemia. Conclusion: In conclusion, this study highlights the role of nutritional status and dietary patterns in anemia prevalence among adolescent girls. Public health interventions should focus on improving dietary quality and addressing both undernutrition and overnutrition. Future research should investigate the effectiveness of iron supplementation programs, the bioavailability of iron in staple diets, and the role of fortified school meals in reducing anemia risk in this population.